The strategy of slang words translation in “the kissing booth” movie subtitle - Lilik Istiqomah; Aulia Ilma Muyasaroh; Ika Lutfiana Muliawati (University of Muhammadiyah Purwokerto, 2019)
This study sets out to describe the translation strategy and the impacts of the strategy to the accuracy and acceptability of slang words translation in “The Kissing Booth” movie subtitle. The research data were collected from “The Kissing Booth” movie file along with the subtitles, both in English and Indonesian. The data were all slang words found in “The Kissing Booth” movie dialogue and subtitle. This study employed descriptive qualitative method to analyze the slang words from the dialogue in the movie. The result of the research shows that the slang words found in the movie are divided into 8 (eight) categories which are: Euphemism with 4 (four) data, Dysphemism with 11 (eleven) data, Typical in Spoken Language with 8 (eight) data, Typical in Informal Situation with 11 (eleven) data, Metaphorical Utterance with 5 (five) data, Proverb with 2 (two) data, Untranslatability with 4 (four) data, and Neutral Syntactic Level with 5 (five) data.